School-Based Peer Effects and Juvenile Behavior - Gaviria, Alejandro; Raphael, Steven (The Review of Economics and Statistics, 2001)
We use a sample of tenth-graders to test for peer-group influences on the propensity to engage in five activities: drug use, alcohol drinking, cigarette smoking, church going, and the likelihood of dropping out of high school. We find strong evidence of peer-group effects at the school level for all activities. Tests for bias due to endogenous school choice yield mixed results. We find evidence of endogeneity bias for two of the five activities analyzed (drug use and alcohol drinking). On the whole, these results confirm the findings of previous research concerning interaction effects at the neighborhood level.